Management of Spittlebugs in Limpograss Pasture - Martin B. Adjei; Richard Sprenkel; Jim Selph (EDIS)
The twolined spittlebug (Prosapia bicincta Say) causes considerable damage to 'Floralta' limpograss (Hemarthria altissima [Poir] Stapf and C.E. Hubb) pastures in south Florida during the summer season. Both adults and immatures or nymphs damage grasses by inserting their needle-like mouthparts and sucking plant juices. The adults also inject toxic saliva into leaf tissue while feeding, which causes streaking on the leaves. Tips of infested grass turn yellow, followed by browning and curling. Heavily infested pasture turns brown, becomes unproductive and may die back in large patches (Figure 1). This document is SS-AGR-106, one of a series of the Agronomy Department, UF/IFAS Extension. Published October 2005.